Journalism and Jim Crow : White supremacy and the Black struggle for a new America - Forde, Kathy Roberts; Bedingfield, Sid; Lichtenstein, Alexander C. (Urbana : University of Illinois Press, 2021)
"White publishers and editors used their newspapers to build, nurture, and protect white supremacy across the South in the decades after the Civil War. At the same time, a vibrant Black press fought to disrupt these efforts and force the United States to live up to its democratic ideals. Journalism and Jim Crow centers the press as a crucial political actor shaping the rise of the Jim Crow South. The contributors explore the leading role of the white press in constructing an anti-democratic society by promoting and supporting not only lynching and convict labor but also coordinated campaigns of violence and fraud that disenfranchised Black voters. They also examine the Black press's parallel fight for a multiracial democracy of equality, justice, and opportunity for all-a losing battle with tragic consequences for the American experiment. Original and revelatory, Journalism and Jim Crow opens up new ways of thinking about the complicated relationship between journalism and power in American democracy. Contributors: Sid Bedingfield, Bryan Bowman, W. Fitzhugh Brundage, Kathy Roberts Forde, Robert Greene II, Kristin L. Gustafson, D'Weston Haywood, Blair LM Kelley, and Razvan Sibii"--
Introduction: Journalism and the world it built -- Part One. Architect of the New South / Kathy Roberts Forde -- Fight for a new America / D'Weston Haywood -- Part Two: Racial terror and disfranchisement -- The press and lynching / W. Fitzhugh Brundage -- Mississippi plan / Robert Greene II -- Part three: Building the Solid South -- Populist insurgency, Alabama / Sid Bedingfield -- Tillman's rebellion, South Carolina -- Death of democracy, North Carolina / Kristin L. Gustafson -- Convict wars, Tennessee / Razvan Sibii -- Tourist empires, Florida / Kathy Roberts Forde and Bryan Bowman -- Part Four. Silencing a generation / Blair LM Kelley -- Epilogue: Journalism and the world to come.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 24, 2021).
JSTOR
Keywords: Journalism -- Southern States -- History -- 19th century; Journalism -- Southern States -- History -- 20th century; American newspapers -- Southern States -- History -- 19th century; American newspapers -- Southern States -- History -- 20th century; African American newspapers -- History -- 19th century; African American newspapers -- History -- 20th century; Journalism -- Political aspects -- Southern States; Racism in the press -- Southern States; Journalisme -- États-Unis (Sud) -- Histoire -- 19e siècle.; Journalisme -- États-Unis (Sud) -- Histoire -- 20e siècle.; Journaux américains -- États-Unis (Sud) -- Histoire -- 19e siècle.; Journaux américains -- États-Unis (Sud) -- Histoire -- 20e siècle.; Journaux noirs américains -- Histoire -- 19e siècle.; Journaux noirs américains -- Histoire -- 20e siècle.; Presse -- Aspect politique -- États-Unis (Sud); Racisme dans la presse -- États-Unis (Sud); SOCIAL SCIENCE / General; African American newspapers; American newspapers; Journalism; Journalism -- Political aspects; Racism in the press; Southern States; 1800-1999; History